ENHANCING AESTHETIC LITERACY IN SCHOOL STUDENTS THROUGH COLOR PAINTING LESSONS - Abdurahmonova Dildora Nizomjon qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines methods to enhance aesthetic literacy in school students through color painting lessons. The study highlights pedagogical approaches aimed at developing students’ creative thinking, visual perception, and understanding of color harmony and composition. Practical exercises, interactive teaching methods, and innovative techniques are emphasized as effective tools to organize lessons, improve students’ engagement, and foster their artistic skills.